Why not to use punch biopsies in formalin-fixed paraffin-embedded samples of prostate cancer tissue for DNA and RNA extraction? - Rafael Parra-Medina (SpringerOpen, 2021)
Abstract Extraction of DNA and RNA from formalin-fixed paraffin-embedded (FFPE) tissue blocks is a critical process in molecular oncology testing. Using FFPE, it is possible to choose the portion of tissue to study, taking into account the cell morphology, storage stability and storage conditions at room temperature, and make retrospective studies with clinical and pathological information. In prostate cancer tissue, in contrast with macroscopic tumors, it is not easy to identify the tumor; therefore, it is very important to make a microscopic diagnosis. We do not recommend punching this tissue because it can choose normal tissue for molecular analysis. In the present article we review the differences between punch biopsy and microdissection.